Spontaneous rupture of a splenic artery aneurysm with hemoperitoneum; case presentation - Vlad Denis Constantin; Ion Motofei; Gelu Valentin Stefanescu; Adrian Silaghi (Journal of Mind and Medical Sciences)
Aneurysms of the splenic artery are relatively rare, being found in patients with portal hypertension, multiparous, atherosclerosis, or in young people with various genetic diseases. In the uncomplicated forms, splenic artery aneurysms are often difficult to diagnose either because of the asymptomatic evolution, or because of the non-specific symptoms. In cases of trauma or large sizes, aneurysms can be complicated by rupture, which can cause hemoperitoneum with the risk of death if specific treatment is not initiated as soon as possible. Depending on the location of the splenic aneurysm, comorbidities, the patient's general condition or lifethreatening complications, laparotomy, laparoscopy, endovascular techniques or combined procedures can be performed. The case of a 33-year-old female patient who presented to the emergency room with abdominal pain, nausea, vomiting and later syncope is presented. The patient was referred to the radiology department, and computed tomography revealed a ruptured splenic artery aneurysm with hemoperitoneum. The splenic artery aneurysm and the spleen were excised by emergency surgery, with a favorable postoperative outcome. The young age of diagnosis and treatment probably implies a genetic component, so that she was referred for additional investigations after discharge.